upaya penyuluhan Bhabinkamtibmas dalam pencegahan kejahatan penipuan di wilayah hukum Polres Kuningan - DONI ARDI SYAPUTRA DONI (Advances in Police Science Research Journal, 2019)
Nowadays there’s a phenomenon in the society. The way of thinking and acting on the community have an impact of crime with advances in technology and knowledge, for example,a crime of fraud. One example of fraud that is rife in Indonesia is the case of online fraud. For the Kuningan resort police jurisdiction, data recorded in 2018 there were 86 fraud cases and 2019 were 96 fraud cases. Bhabinkamtibmas functions to prevent and resolve problems by prioritizing communication with information technology that is increasingly advanced and impossible to hold, efforts to prevent fraud in the community must be done and improved. This study aims to determine the efforts of Bhabinkamtibmas in the prevention of fraud crime andfactors that influence Bhabinkamtibmas in the prevention of fraud crime in the Kuningan police jurisdiction. This study uses a qualitative research with descriptive analysis research. This research is located in Kuningan Sector Police. Data collection techniques using interviews, observation and document review. The data validity used in this study are triangulation of sources, techniques, time and theory. The result of this study is Bhabinkamtibmas role to prevent fraud crime in the Kuningan sector police has been running well. External factors that affect the Bhabinkamtibmas are that the community has participated and supported in preventing this proactively while the internal factorsare the human resources of the members of Bhabinkamtibmas itself, where total members of the Kuningan sector police are still lacking. When viewed from the infrastructure obtained by Bhabinkamtibmas is still lacking.